Obvladovanje poslovnih in strateških kriz s projektnim managementom - Vrečko, Igor (Projektna mreža Slovenije, 2007)
Someone call contemporary business environment as "new economy", someone as "business of the third century" and others with other names. But they all have in common cognition, that the management process in companies and other organizations is more complex as it was in the past times. The change is specially expressive in changes itself, to which we are exposed and to which we try to adapt or even out pass them if we would like to stay success in our working. Of course it is not simple and that is the reason for appearance of different forms of crisis which appear in business systems and which can actually be expected. Project management is a concept, is a tool, is a way - it is an answer for management to successfully master dynamic changes of business environment with strategic adaptation of business system.
Keywords: krize; krizni management; podjetja; poslovna strategija; projektno vodenje; strateški management